2010
DOI: 10.1097/cco.0b013e32833c06da
|View full text |Cite
|
Sign up to set email alerts
|

Current controversies in the management of patients with early-stage vulvar cancer

Abstract: Sentinel node biopsy is safe in treatment of early-stage vulvar cancer. Ongoing studies are investigating the optimal additional treatment for patients with a positive sentinel node in terms of efficacy and morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15] The results of this study also verified that LN involvement was clearly confirmed as being the most important prognostic factor for both DFS. In the multivariate analysis, LN involvement was the independent prognostic factor regarding DFS in the current study.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…[7][8][9][10][11][12][13][14][15] The results of this study also verified that LN involvement was clearly confirmed as being the most important prognostic factor for both DFS. In the multivariate analysis, LN involvement was the independent prognostic factor regarding DFS in the current study.…”
supporting
confidence: 71%
“…19 However, the negative effect of single LN involvement on DFS was also shown by other researchers. 13,20 According to our clinical protocols, one metastatic LN was sufficient for the indication of adjuvant therapy. All patients with positive LNs were candidates for adjuvant therapy in the current study.…”
Section: International Journal Of Hematology and Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial clinical benefit of adjuvant radiotherapy has been clearly demonstrated for patients with two or more lymph-node metastases, whereas the role of radiation in patients with a single intracapsular metastasis remains controversial [Homesley et al 1986;Oonk et al 2010]. Fons and colleagues could not demonstrate a benefit of adjuvant radiotherapy in patients with only one affected lymph node regarding overall or disease-free survival [Fons et al 2009].…”
Section: Recommendations For Radiotherapy In Intermediate-stage Vulvamentioning
confidence: 99%
“…In the literature as a risk factors predicting vulvar cancer recurrrence have been described also intracapsular lymph-node metastasis, lymphangio invasion and large primary tumours (Burger et al, 1995;Woelber et al, 2009;Oonk et al, 2010). To get clear conclusions of vulvar cancer prognostic factors, large multicentric, prospective trial with uniform treatment approache is needed.…”
mentioning
confidence: 99%